Late Quaternary changes in bat palaeobiodiversity and palaeobiogeography under climatic and anthropogenic pressure: new insights from Marie-Galante, Lesser Antilles. (1st July 2016) - Stoetzel, Emmanuelle; Royer, Aurélien; Cochard, David; Lenoble, Arnaud
Abstract: Data on Lesser Antillean Late Quaternary fossil bat assemblages remains limited, leading to their general exclusion from studies focusing on Caribbean bat palaeobiodiversity and palaeobiogeography. Additionally, the role of climatic versus human pressure driving changes in faunal communities remains poorly understood. Here we describe a fossil bat assemblage from Blanchard Cave on Marie-Galante in the Lesser Antilles, which produced numerous bat remains from a well-dated, stratified context. Our study reveals the occurrence of at least 12 bat species during the Late Pleistocene and Early Holocene on Marie-Galante, whereas only eight species are currently known on the island. Among these 12 species, six are extirpated and one is extinct. Faunal changes within the Blanchard sequence indicate variations in Pleistocene bat species representation in the Lesser Antilles to have been influenced by climatic conditions, with "northern species" (Greater Antilles) favored during glacial conditions and "southern species" (southern Lesser Antilles) during interglacial events. However, few species disappeared at the end of the Late Pleistocene, with most of the extinction/extirpation events occurring during the Holocene. This pattern suggests human activities in the Lesser Antilles to have played a major role in bat turnover during the late Holocene. Highlights: A new, important fossil bat assemblage from the Lesser Antilles was studied. Faunal changes were observed in a well-dated stratigraphic context. Past Lesser Antillean bat faunas were more diversified and different to current ones. The Greater Antillean component was particularly important. Human pressure seems to have had a more prominent role than climatic changes.